Examining the effect of reduced action capabilities on defensive anticipation in a 1-vs-1 task. Issue 3 (3rd July 2021) - Wilson, Ricky; Alder, David; Dicks, Matt; Poolton, Jamie
ABSTRACT: This study used small-sided games (SSGs) to induce fatigue and therefore, reduce the action capabilities of Varsity soccer players ( n = 20). The aim was to examine the effect of compromised action capabilities on defensive movement response in a 1-vs-1 scenario. Action capabilities were assessed via countermovement jumps (CMJ), 5-m acceleration, 20-m sprint and a Change of Direction (COD) test. Defensive movement response was measured via a Soccer-Specific Anticipation Test (SSAT). Following SSGs, significant reductions were observed in jump ( p =.04, d =.31), acceleration ( p <.001, d =.98), and sprint ( p <.001, d =.66) performance. Significantly, players tended to move earlier in the SSAT following SSGs ( p =.049, d= .66). Furthermore, to examine the distinct effect of reductions in each action capability, players were categorised according to whether SSGs had a worthwhile change in CMJ, acceleration, sprint or COD performance. For each of the four measures, movements tended to be initiated earlier following SSGs, although pre-/post-SSGs differences were not significant ( p =.08-.51), moderate to large effect sizes were shown ( d =.56-.84). These findings intimate that compromised action capabilities influence the timing of the movement response of defensive players in 1-vs-1 situations.